Justice at war : civil liberties and civil rights during times of crisis - Delgado, Richard (New York University Press, 2003)
The status of civil rights in the United States today is as volatile an issue as ever, with many Americans wondering if new laws, implemented after the events of September 11, restrict more people than they protect. How will efforts to eradicate racism, sexism, and xenophobia be affected by the measures our government takes in the name of protecting its citizens?. Richard Delgado, one of the founding figures in the Critical Race Theory movement, addresses these problems with his latest book in the award-winning Rodrigo Chronicles . Employing the narrative device he and other Critical Race theo.